(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: The efficiency of the administrative offices at the district office Manado city Malalayang indication has not been effective. Moving on from the problems encountered is the lack of utilization of human resources employee, inadequate facilities and budget are still minimal. The purpose of this study was to determine how the efficiency of office administration at the sub-district office Malalayang City Research using qualitative methods. The informants as many as eight employees in the District Government Officials namely Subscript Head, Secretary of Sub district Head, Head of Divisions, 2 Head of Section , and 2 Staff / implementers. Collecting data with interview techniques; while the data were analysed using qualitative analysis techniques interactive model of Miles and Hubernann. Based on the results of the study it can be concluded: (1) The efficiency of the administrative offices at sub-district Office Malalayang Manado City are generally good, but not maximum views of the realization of the achievements of the realization of the budget, the utilization of human resource potential employees as competence, use of facilities / infrastructure and equipment and supporting facilities, and the mechanisms and procedures for the implementation of an office job. (2) Programs and activities of the work / office administration services that have been defined in the planning of the work / performance at each fiscal year can generally be carried out and the realization of the results is good / satisfactory, but not optimally. This means that the use of resources in the implementation of the work / office administration services can provide good work / unsatisfactory. Keywords: efficiency, administrative offices.